The Analyzing Factors Influencing Continuance Intention to Use E-Wallet in Generation Y and Z - Mas Ayu Dewi; Sarana Sarana; Ahmad Wafa Mansur; Prima Ayundyayasti (Cita Konsultindo Research Center, 2023)
This study aims to analyze factors influencing continuance intention to use e-wallet in generation Y and Z. The data used is primary data obtained by distributing questionnaires through the Google Form. The number of samples in this research is 210 respondents using a purposive sampling method. The data analysis technique used is the Structural Equation Modeling (SEM). The results of this study indicate that perceived benefits have a positive significant effect and perceived risks have a negative significant effect on continuance intention to use E-wallet. Perceived benefit has a stronger effect than perceived risk. Users will use E-wallet if the perceived benefit is greater than the perceived risk. Perceived benefit factors include economic benefits, seamless transactions, and convenience which has a positive significant effect on perceived benefits. Convenience has the strongest effect on perceived benefit. Perceived risk factors include financial risk, legal risk, and security risk which has a positive significant effect on perceived risk. Financial risk has the strongest effect on perceived risk.